Anterior Rectal Resection in a Patient with Aortoiliac Occlusive Disease and Coexisting Collateral Pathways: Management and Pitfalls - Floryn Cherbanyk; Jean-Loup Gassend; Olivier Martinet; Snezana Andrejevic-Blant; Henri-Marcel Hoogewoud (Case Reports in Surgery)
Chronic aortoiliac occlusive disease most often affects the common iliac arteries and distal aorta but can progress all the way to the renal arteries, occluding the inferior mesenteric artery. A compensatory collateral network typically develops to preserve lower body perfusion. Inadvertent compression or ligation of such collaterals during surgery can have catastrophic consequences. In this article, we present the case of a 63-year-old patient with aortoiliac occlusive disease, requiring surgery for an adenocarcinoma of the rectosigmoid junction. A CT angiography was performed in order to map out the collateral pathways that had developed and Doppler ultrasound was used to mark their positions. The surgical procedure was adapted to his specific anatomy. A successful anterior resection was performed, and the patient made an uneventful recovery. In cases of aortoiliac obliteration, the existence of collaterals must be kept in mind and investigated with a multidisciplinary approach before any surgery is considered.